2007
DOI: 10.1038/sj.npp.1301506
|View full text |Cite|
|
Sign up to set email alerts
|

Cannabis Use Disrupts Eyeblink Conditioning: Evidence for Cannabinoid Modulation of Cerebellar-Dependent Learning

Abstract: While the cerebellum contains the highest density of cannabinoid receptor (CB1) in the brain, no studies have assessed the effect of exogenous cannabinoids on cerebellar-dependent learning in humans. The current study, therefore, examined the effect of chronic cannabis use on classical eyeblink conditioning (EBC), a cerebellar-mediated task which has been shown to be disrupted in CB1 knockout mice. Chronic cannabis users (24 h abstinence before study; positive THC urine drug test) free of DSM-IV Axis-I or -II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 67 publications
2
70
2
Order By: Relevance
“…Previous research using a single-cue delay EBC paradigm found deficits in clinical groups with conditions including schizophrenia Brown et al, 2005), bipolar disorder (Bolbecker, Mehta, Johannesen, et al, 2009), and drug abuse (Skosnik et al, 2007). However, few studies involving the CS-US ISI have been completed, and none involving clinical groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research using a single-cue delay EBC paradigm found deficits in clinical groups with conditions including schizophrenia Brown et al, 2005), bipolar disorder (Bolbecker, Mehta, Johannesen, et al, 2009), and drug abuse (Skosnik et al, 2007). However, few studies involving the CS-US ISI have been completed, and none involving clinical groups.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, concomitant frontocentral electroencephalographic (EEG) recording data were made in order to assess eventrelated potentials (ERPs) to the tone CS during EBC. It has recently been shown that a tone CS during EBC elicits a robust N100-P200 ERP complex (Edwards et al, 2008;Skosnik et al, 2007), which is known to be generated in the auditory cortex and is sensitive to attention allocation (Coull, 1998;Hillyard, Hink, Schwent, & Picton, 1973). In animals, the auditory cortex has been shown to exhibit electrophysiological changes that are related to conditioning (Kraus & Disterhoft, 1982).…”
mentioning
confidence: 99%
“…Both the knockout and the antagonist caused a deficit in acquisition of dEBC. Moreover, Skosnik et al (2008) found that human subjects who chronically used cannabis and may have down-regulated CB1Rs showed similar deficits in the acquisition of dEBC when not intoxicated. Taken together, these results suggest that CB1Rs play an important role in acquisition of dEBC.…”
mentioning
confidence: 99%
“…Following repeated CS-US trials, a conditioned response (CR) that preceded US onset was measured. In humans, repeated THC intake has previously been shown to markedly reduce the incidence and timing of this neuronal adaptive response (10). Here, Cutando et al (9) found in mice that the THC-induced behavioral impairment was related to the rapid and strong downregulation of CB 1 receptors.…”
Section: Consequences In the Blink Of An Eyementioning
confidence: 77%